Business strategy, environmental variables, and performance of hotels in Batam City, Indonesia / Agus Riyadi - Riyadi, Agus (2009)
In the previous years, the numbers of tourists visiting Batarn city have been fluctuating. According to The Indonesian Statistic Bureau records, 1,526,094 tourist visited Batarn city in 2004, 1,024,733 in 2005 and 1,012,536 in 2006 (BPS, 2007). The decreased in tourist receipts contradicted with numbers of hotel rooms whereby many new hotels have been constructed, and there has been an increased competition among the hotels. There were more than 6,725 hotel rooms in 2004 in Batarn city and increase 7,097 hotel rooms in 2005 (BPS, 2007). The increase of hotel industry in Batarn city in recent decades pre-empted a growth in national and international hotel chains, and lately the emergence of global chains. The growth has not only occurred in the number of chains, but also in their size and segment market especially from Singapore and Malaysia. The highly volatile and competitive business environment has encouraged the hotel industry in Batarn to provide a high standard of quality services to the customers. Problems arise when the flow of resources becomes uncertain due to unpredictable changes in the environment. These changes are assumed to have an immediate impact on the hotel industry's rate of growth and performance. This research aims to study the area of improving a hotel manager's performance by identifying the working environment variables, which affect his strategy. The main objective of this study is to explore the strategic dimensions, the degree of environmental variables, the relationship between business strategy, environmental variables and performance utilized by hotels in Batarn city.